A Longitudinal Examination of Positive Parenting Following an Acceptance-Based Couple Intervention - Morrill, Melinda Ippolito (J Fam Psychol, 2015)
Positive parenting practices have been shown to be essential for healthy child development, and yet have also been found to be particularly challenging for parents to enact and maintain. This paper explores an innovative approach for increasing positive parenting by targeting specific positive emotional processes within marital relationships. Couple emotional acceptance is a powerful mechanism that has repeatedly been found to improve romantic relationships, but whether these effects extend to the larger family environment is less well understood. The current longitudinal study examined the role of improved levels of acceptance in mother’s and father’s positive parenting after a couple intervention. Participants included 244 parents (122 couples) in the Marriage Checkup (MC) study, a randomized, controlled, acceptance-based, intervention study. Data indicated that both women and men experienced significantly greater felt acceptance two-weeks after the MC intervention, treatment women demonstrated greater positive parenting two weeks after the intervention, and all treatment participants’ positive parenting was better maintained than control couple’s six months later. Importantly, although mothers’ positive parenting was not influenced by different levels of felt acceptance, changes in father’s positive parenting were positively associated with changes in felt acceptance. As men felt more accepted by their wives, their levels of positive parenting changed in kind, and this effect on positive parenting was found to be mediated by felt acceptance two weeks after the MC. Overall, findings supported the potential benefits of targeting couple acceptance to generate positive cascades throughout the larger family system.